Pemberdayaan Kreator Lokal dan Tata Kelola untuk Pariwisata Desa yang Berkelanjutan di Kabupaten Bandung - Fery Wijayanto; Lala M. Kolopaking; Rina Mardiana (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
Bandung Regency Regional Regulation Number 7 of 2020 regarding the development of 100 tourism villages does not explicitly regulate the governance mechanism of tourism villages. Effective governance requires the involvement of individuals as local creators who are capable of initiating and sustaining tourism village management. This study aims to identify the qualities of local creators in driving tourism village governance and determining the sustainability of tourism village communities in Bandung Regency. This research employs a qualitative approach using primary data through observation, interviews, and focus group discussions, as well as secondary data obtained from village records. The informants consist of 23 individuals analyzed at the individual level. Data analysis includes the stages of data reduction, data display, verification, and conclusion drawing. The findings reveal that local initiators with strong leadership, education, experience, capacity, and innovative initiatives serve as local creators capable of mobilizing tourism village governance mechanisms. They operate through penta-helix collaboration, role-sharing dialogues, and profit distribution to ensure community sustainability. Community sustainability is marked by regional and national achievements based on indicators such as increasing tourist numbers, economic gains, and culturally and environmentally based development. Local creators and governance structures interact dynamically to ensure the long-term sustainability of tourism village communities. In conclusion, competent local creators act as key agents in driving adaptive and transformative governance mechanisms that ensure the sustainability of rural tourism communities in Bandung Regency.